CoSe2 nanoparticles anchored on dual 1D carbon nanotubes/N-doped carbon nanofibers as high-performance anodes for sodium-ion storage. Issue 16 (28th March 2023) - Jiang, Qilei; Han, Xu; Zhang, Mengling; Qin, Zheng; Huang, Xianggang; Hou, Yan; Cao, Xueqin; Lang, Jian-ping; Gu, Hongwei
Abstract : Dual 1D CoSe2 @CNTs/N-CNFs obtained by electrospinning and subsequent two-step heating process exhibit superior sodium-ion storage performance when used as the anode of an SIB. Abstract : Transition metal chalcogenides (TMCs) have been widely explored and utilized in sodium-ion battery (SIB) anodes owing to their unique advantages, such as high theoretical specific capacity and low cost. However, their inherent defects, such as low electronic conductivity and severe volume expansion, seriously limit the further development of TMC-based anodes. Here, a novel composite material of CoSe2 nanoparticles (NPs) encapsulated in a dual one-dimensional (1D) carbon composite structure (CoSe2 @CNTs/N-CNFs) was designed deliberately. Carbon nanotubes (CNTs) were grown in situ on the surface of carbon nanofibers (CNFs) with eco-friendly ethanol as the carbon source, while electrospun polyacrylonitrile (PAN) fibers were pyrolyzed to form nitrogen-doped nanofibers. It is noted that the wrapping with the composite carbon structure greatly improved the stability of CoSe2 NPs and solved its inherent defects as an anode material. When assembled into a half-cell, the CoSe2 @CNTs/N-CNFs electrode exhibited outstanding sodium storage performance with a reversible specific capacity of 442 mA h g −1 after 100 cycles at 0.1 A g −1, as well as excellent rate performance, and the discharge specific capacity still reached 265 mA h g −1 even after 2000 cycles at a high current density of 5 A g −1 . This study shows a new way to build a novel carbon substrate and TMC composite sodium storage material with low cost.